THE NEXUS BETWEEN TRADE OPENNESS AND ENVIRONMENTAL DEGRADATION : A VECM ANALYSIS - Wicaksana, Tania; Widodo, Wahyu (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This research aimed to analyze the influence of trade openness, ICT, per capita income, and Human Development Index on environmental quality in Upper-Middle Income countries in the short and long term and how per capita income influenced environmental quality in the U-shaped EKC hypothesis in Upper-Middle Income countries over the 1990-2020 periods using the VECM Panel analysis. Several findings were revealed in this research. First, the coefficient of trade openness in the long-term and short-term on environmental quality was positive and statistically significant at the 1% level. Second, the relationship between ICT and environmental quality had a positive influence in the short term and a negative influence in the long term. Third, the relationship between per capita income and environmental quality positively influenced the long- and short-term. In these findings, an increase in per capita income increased carbon dioxide, which caused a decrease in environmental quality and emerged an inverted U relationship in the long- and short-term of the EKC hypothesis in UMI countries, with the turning point in the short-term being US 728,530 and in the long-term US 772,839. Finally, the Human Development Index in this research positively influences environmental quality in the short- and long-term. The outcomes of this study have considerable Policy implications regarding trade openness policy formulation to reduce environmental degradation, especially in Upper Middle-Income Countries.